2014
DOI: 10.1590/s1517-83822014000400033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial properties of Barium Zirconate Titanate (BZT) nanoparticle

Abstract: So far, the antibacterial activity of some organic and inorganic compounds has been studied. Barium zirconate titanate [Ba(ZrxTi1-x)O3] (x = 0.05) nanoparticle is an example of inorganic materials. In vitro studies have provided evidence for the antibacterial activity of this nanoparticle. In the current study, the nano-powder was synthesized by sol-gel method. X-ray diffraction showed that the powder was single-phase and had a perovskite structure at the calcination temperature of 1000 °C. Antibacterial activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Furthermore, the rst endothermic peaks for BaFeO 3 -Cop and BaFeO 3 -Sol samples at 613 and 624 K, respectively. These peaks may be due to the formation of BaFeO 3-δ perovskite while the second small endothermic peak at 650 K for BaFeO 3 -Cop sample may be due to impurity (BaO) formation which is observed in XRD and DLS results for BFO-Cop sample [14,22]. The BaFeO 3-δ perovskite phase begins to appear in BaFeO 3 -Cop sample at lower temperature than the BaFeO 3 -Sol sample because of the chemical nature of the used solvant in the precipitate [25].…”
Section: Mössbauer and Xps Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, the rst endothermic peaks for BaFeO 3 -Cop and BaFeO 3 -Sol samples at 613 and 624 K, respectively. These peaks may be due to the formation of BaFeO 3-δ perovskite while the second small endothermic peak at 650 K for BaFeO 3 -Cop sample may be due to impurity (BaO) formation which is observed in XRD and DLS results for BFO-Cop sample [14,22]. The BaFeO 3-δ perovskite phase begins to appear in BaFeO 3 -Cop sample at lower temperature than the BaFeO 3 -Sol sample because of the chemical nature of the used solvant in the precipitate [25].…”
Section: Mössbauer and Xps Studiesmentioning
confidence: 87%
“…The perovskite nanomaterials as antibacterial and antibio lm agent is a new and growing area in the eld of medicine because of the size of bacterial cell and its membranes are micrometers and nanometers sizes, respectively [12]. Less expensive perovskite nanomaterials were used as antibacterial agent such as SrFeO 3-δ , SrTi 1-x Fe x O 3 (x=0, 0.2, 0.4, 0.6, 0.8 and 1) and Ba(Zr x Ti 1-x )O 3 (x=0.05) [10,13,14]. Abdel-Khalek et al [10] investigated the microorganisms test, antimicrobial activity as well as minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the SrFeO 3-δ nanoparticles sample.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a comprehensive global effort has been recently started to reduce hazardous wastes of chemical origin in addition to developing economical, cost-effective, and safe method for analysis of chemicals and toxicants in the reference laboratories as well as in clinical practices for diagnostic purposes [13]. In addition, to overcome the disadvantages of routine microextraction technique, recent studies have focused on developing green methods with the lowest solvent use as possible using biocompatible nanomaterials [14]. For this reason, plant extracts or other purified herbal products are the era of interest for many researchers in green chemistry or diagnostic medicine, and recent findings showed that herbal products or plant extract can be used at different stages of method development [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology is an interdisciplinary science that links different scientific fields, including medical and pharmaceutical technology, physics, engineering, and chemistry (1). Nanoparticles (NPs) are small-sized particles with typical dimensions of 1 -100 nm (2,3). Due to the small size of NPs, they can interact with a variety of biomolecules, including proteins and nucleic acids (4).…”
Section: Introductionmentioning
confidence: 99%